Understanding Patient Perspectives in Treatment and Management of Care in Asthma - Hicks A; George MJ; Benjamin M; Lacoste E; Orr HC; Melendez A; Gardner DD (Patient Preference and Adherence)
Alexandra Hicks,1 Michael J George,2 Mason Benjamin,2 Eric Lacoste,3 Hilarry C Orr,4 Angel Melendez,5 Donna D’laine Gardner6 1Immunology and Inflammation Research Therapeutic Area, Sanofi, Cambridge, MA, USA; 2Patient Informed Development and Health Value Translation, Sanofi, Bridgewater, NJ, USA; 3Global CMC Development, Sanofi, Vitry-sur-Seine, France; 4Patient Author, New Philadelphia, OH, USA; 5Patient Author, El Paso, TX, USA; 6Allergy and Asthma Network, Fairfax, VA, USACorrespondence: Alexandra Hicks, Sanofi, 350 Water Street, Cambridge, MA, 02141, USA, Tel +1-781-663-9499, Email alexandra.hicks@sanofi.comPurpose: For the development of novel and efficacious drugs and improvement of patients’ quality of life, the involvement of patient stakeholders in drug development is essential. This study was conducted among patients with asthma to understand their unmet needs with current treatments, and expectations from new treatments.Methods: Sanofi collaborated with the Allergy & Asthma Network (AAN), a US-based patient advocacy group and their patient community. Several virtual patient panels were conducted involving patient advocates and researchers that spanned patient experiences with asthma, treatment options, gaps, needs, and priorities. Additionally, a literature search was conducted using Medline® between July 2013 and July 2023.Results: Based on input gleaned from patients (n=5), their major unmet needs included: management of medication-related side effects, lack of information about correct inhaler techniques, medication costs, misunderstanding of medication dosing schedules, lack of communication between researchers and patients, lack of awareness about patient advocacy organizations and research led programs, and fear of discrimination or having concerns disregarded by healthcare providers. Patients expressed their expectation that new treatments should treat all asthma symptoms, including inflammation, airway constriction, and responsiveness to asthma triggers, all with a single treatment. For patients, an ideal treatment would not need to be taken daily, would be quick-acting, and cost-effective for all patients regardless of their insurance status or coverage. Digital applications that remind patients to take their medications on schedule and monitor asthma triggers, mood, sleep, peak flow recordings, and nutrition could improve patients’ treatment adherence, quality of life, and health outcomes would be welcomed.Conclusion: This study emphasizes the importance of gathering input from patients living with asthma, understanding their unmet needs, and the importance of integrated patient engagement in the development of new therapies for asthma.Plain Language Summary: It is important for drug companies, scientists, and individuals with asthma to work together to make medicines that truly help patients. Sanofi, a drug company, worked with the Allergy and Asthma Network (AAN), a patient advocacy group that advocates for people with asthma. Sanofi and AAN held online meetings for patients and researchers to discuss how asthma is treated, what is missing in the treatment landscape, and what is most important to patients. They also reviewed information from asthma studies.Patients were concerned about side effects from their medicines, understanding the right use of inhalers, medication costs, dose scheduling, limited interaction with researchers, insufficient knowledge about patient advocacy groups, and feeling ignored by health care providers.Patients want new all-in-one medicines for asthma which reduce swelling, open the airways, and prevent asthma flares when exposed to triggers. They desire medicines which are not taken daily, work quickly, are inexpensive, and easy to get covered by insurance.Mobile applications can remind patients to take medicine and keep track of asthma triggers, how they feel, their sleep, and what they eat. Teaching patients with asthma management resources, programs that help afford medicine, routine breathing tests, and regular check-ups can make a big difference in asthma care.The information collected from patients during online meetings has also helped Sanofi design better medicines for asthma by integrating patient priorities into its development programs, designing less burdensome clinical trials, and generating the types of data patients say are most important and relevant to them.Keywords: asthma, patient advocacy groups, patient-focused drug development